Determining optimal strategies for primary prevention of cardiovascular disease: systematic review, cost-effectiveness review and network meta-analysis protocol - Uthman, Olalekan A. (Syst Rev, 2020)
BACKGROUND: Despite recent improvements in the burden of cardiovascular disease (CVD) in the UK, deaths from CVD are relatively high compared with other high-income countries. An estimated 7 million people in the UK are living with CVD, and the healthcare cost is approximately £11 billion annually. In more than 90% of cases, the risk of a first heart attack is thought to be related to modifiable risk factors including smoking, poor diet, lipidemia, high blood pressure, inactivity, obesity and excess alcohol consumption. The aim of the study is to synthesise evidence for the comparative effectiveness and cost-effectiveness of different interventions for the primary prevention of CVD. METHODS: We will systematically search databases (for example, MEDLINE (Ovid), Embase (Ovid), Cochrane Library) and the reference lists of previous systematic reviews for randomised controlled trials that assess the effectiveness and cost-effectiveness of any form of intervention aimed at adult populations for the primary prevention of CVD, including but not limited to lipid lowering medications, blood pressure lowering medications, antiplatelet agents, nutritional supplements, dietary interventions, health promotion programmes, physical activity interventions or structural and policy interventions. Interventions may or may not be targeted at high-risk groups. Publications from any year will be considered for inclusion. The primary outcome will be all cause mortality. Secondary outcomes will be cardiovascular diseases related mortality, major cardiovascular events, coronary heart disease, incremental costs per quality-adjusted life years gained. If data permits, we will use network meta-analysis to compare and rank effectiveness of different interventions, and test effect modification of intervention effectiveness using subgroup analyses and meta-regression analyses. DISCUSSION: The results will be important for policymakers when making decisions between multiple possible alternative strategies to prevent CVD. Compared to results from existing multiple separate pairwise meta-analyses, this overarching synthesis of all relevant work will enhance decision-making. The findings will be crucial to inform evidence-based priorities and guidelines for policies and planning prevention strategies of CVD. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42019123940.